Performance of Free Water Surface Constructed Wetlands (FWS-CWs) using Water Jasmine (Echinodorus palaefolius) in Removing COD and TDS from Domestic Wastewater - Mutiara Fajar; Dinda Yuliana Nola Ujung; Erlina Kurnianingtyas; Tarmizi Taher (Indonesian Journal of Environmental Management and Sustainability, 2026)
This study evaluated the reduction of chemical oxygen demand (COD) and total dissolved solids (TDS) in domestic wastewater using water jasmine (Echinodorus palaefolius) in a free water surface constructed wetland (FWS-CW) system. We characterized the influent wastewater, assessed the acclimatization of E. palaefolius to undiluted domestic wastewater, and quantified the effects of plant density and observation time on COD and TDS removal. The experimental campaign comprised wastewater sampling, reactor fabrication, plant acclimatization, batch treatment, and analyses of COD and TDS. Removal efficiencies were computed and the data analyzed by two-way ANOVA followed by Tukey’s HSD post-hoc test. The initial wastewater contained 275.88 mg/L COD and 286 ppm TDS. Echinodorus palaefolius adapted successfully to the wastewater and reached maximum removal efficiencies of 86.04% for COD and 12.41% for TDS in the 12-plant reactor on Day 12. The two-way ANOVA showed significant main effects of plant density and observation time on both parameters (p < 0.05), and Tukey’s HSD indicated that the presence of E. palaefolius significantly improved TDS removal compared with the unplanted control, although differences among the 4-, 8-, and 12-plant reactors were not statistically significant. These findings indicate that even moderate plant densities are effective for reducing COD and TDS in tropical domestic wastewater treated with FWS-CWs.